Enhancing Science Communication Skills for Future Science Teachers: A Redesign of Inquiry-Based Learning - Pruekpramool, Chaninan; Suwansil, Pusanisa (Science Essence Journal, 2024)
Science communication skills are crucial for science teachers but are often neglected in traditional inquiry-based learning. This study addresses this gap by revising the inquiry-based learning model to integrate communication strategies, aiming to promote the science communication skills of pre-service science teachers in Thailand. The study involved 25 third-year pre-service science teachers enrolled in a science program at a Rajabhat University in central Thailand. Research instruments included lesson plans, science communication skills tests, and a science learning achievement test. Data analysis was conducted using percentage, mean, standard deviation, relative gain score, and a t-test for dependent samples. The redesigned inquiry learning model featured five steps: engagement, exploration and inference, logical explanation, analytical elaboration, and evaluation. Results showed that after learning with this model, pre-service teachers achieved the highest mean scores in summarizing scientific concepts, followed by interpreting data with scientific evidence, and explaining scientific phenomena. Additionally, the relative gain scores of science communication skills increased significantly, moving from moderate to very high levels across seven phases. The posttest mean score for science learning achievement was also significantly higher than the pretest score. This innovative approach demonstrates the potential of combining inquiry-based learning with communication strategies to effectively enhance the science communication skills and overall learning achievements of future science teachers.